The English History Play in the age of Shakespeare. - Ribner., Irving (Taylor and Francis, 2013)
First published in 1957. This edition re-issues the second edition of 1965. Recognized as one of the leading books in its field, The English History Play in the Age of Shakespeare presents the most comprehensive account available of the English historical drama from its beginning to the closing of the theatres in 1642 and relates this development to Renaissance historiography and Elizabethan political theory.